A secure data authentication in wireless body area network for health monitoring using electrocardiogram-based key agreement - Ramli, Sofia Najwa; Ahmad, Rabiah; Abdollah, Mohd Faizal (Praise Worthy Prize, 2016)
Wireless Body Area Network (WBAN) comprises of a set of biomedical sensors, which are implanted into or placed around a human body to serve a variety of network applications constantly. One of the applications, the ubiquitous health monitoring, has improved the ability of healthcare providers to deliver appropriate treatments to the patients either in hospitals or at homes. As the need of this application increases, several security issues also arise due to the nature of open wireless medium. Moreover, implementing an effective security mechanism uses a significant part of the available energy in a WBAN, whereby the sensors have limited resource constraints in terms of power consumption and memory space. Thus, this paper presents a new authentication protocol model that utilizes Electrocardiogram (ECG) signal as biometric as well as cryptographic key to ensure that the transmitted data are originated from the required WBAN. Due to the uniqueness and the permanence property of ECG signal, the proposed model is developed to achieve optimal security performance and required lightweight manners of to the resource-limited biomedical sensors. The simulation system is implemented based on the process of an improved fuzzy vault scheme with a new error correction algorithm, which results in reducing computational complexity, communication load and storage overhead when compared to several previous work